Implementasi Program Menghafal Al-Qur’an dan Hadis Arba’in di SMAIT Insan Madani 8 Tangerang Selatan - Istiqomah, Siti; Aini, Safirotul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
This research is motivated by the lack of interest in Islamic educational institutions that implement programs to memorize the Qur'an and hadith. One of the aims of this program is to create a righteous generation. This study aims to describe the memorization program of the Qur'an and Arba'in Hadith at SMAIT Insan Madani 8, South Tangerang. The research method used in this study is a qualitative approach with a descriptive type. The data sources used are primary data sources, namely school principals, tahfizh teachers, arba'in hadith teachers, students in class X and XI, and secondary data sources in the form of books, journals, and theses. Data collection techniques in this study using observation, interviews, and documentation. The results of this study indicate that the implementation of the Al-Qur'an memorization program at SMAIT Insan Madani 8 South Tangerang has a target of memorizing 28, 29, and 30, with a minimum of 29 chapters. Each class gets 60 minutes and 1 time in 1 week and is carried out in school hall. This tahfizh learning uses the talaqqi method, and uses media in the form of a connecting book which contains school rules, al-ma'tsurat, chapters 28, 29, 30, as well as students' memorization agendas. While the arba'in hadith memorization program has a target of at least 10 hadith students per year. This learning uses the talaqqi method and the drill method, so that students try to read and explain the contents. The supporting factors of the program of memorizing the Qur'an and arba'in hadith at SMAIT Insan Madani 8 South Tangerang, namely, school principals, educators, facilities and infrastructure, support from people around, choosing the right time, giving rewards and sanctions.